The Role of Special Education Teachers in Developing Children's Social Values - Al-Wahaily, M. M. Hadeel Hassan Khalaf Al-Wahaily (Sulaimani Journal for Humanities, 2026)
Teachers play a significant role in shaping a child's culture and developing their personality. They complement the family's role in the socialization process and have a direct impact on children regarding their attitudes and intellectual and academic levels. During the kindergarten and primary school stages, a child's personality, attitudes, and inclinations are formed; thus, there is a need to understand the teacher's role in developing social values for children. The interest in studying values is of utmost importance as it aids in developing curricula for all educational stages. Its importance is also evident in raising family awareness of their responsibility towards their children's development of desired social values. Furthermore, it guides teachers in all educational institutions, especially in early stages, on their role in shaping children's personalities and modifying their behavior, as well as supporting what is acceptable and desirable.
Keywords: teacher; special education; development; social values; child